The Efficacy of the Consumption of Manalagi Apples and Fuji Apples on Decreasing Plaque Index in Students of Madrasah Aliyah Al-Hidayah Labuhan Batu Selatan, North Sumatra - Molek; Dwi Setya Rini; Mangatas Halomoan Parluhutan Hutagulung (HM Publisher, 2021)
Caries is a common oral and dental disease. The main etiology of caries is plaque. Chewing fibrous fruits can prevent plaque accumulation, including Manalagi apples and Fuji apples. The purpose of this study was to determine the differences in the effectiveness of consuming manalagi apples with fuji apples on the reduction of the plaque index in Madrasah Aliyah Al-Hidayah students. This type of research is a quasi-experimental design with pre-test and post-test control groups. The total sample was 32 students aged 16-18. Data were analyzed by statistical test T-Test. Based on the results of the paired t-test statistical test, it was found that the average plaque index before chewing an apple was 0.63 ± 0.42 after 0.26 ± 0.26 with a mean of 0.37 ± 0.16. Meanwhile, the plaque index before chewing on Fuji apples was 1.01 ± 0.59 after 0.87 ± 0.54 with a mean of 0.14 ± 0.05. The results of the independent statistical t-test showed that the value of p = 0.001, which means that there is a difference in chewing Manalagi apples with Fuji apples to decrease the plaque index. The conclusion of this study is that consuming manalagi apples is more effective than fuji apples in reducing the plaque index